2017
DOI: 10.1186/s40991-017-0022-z
|View full text |Cite
|
Sign up to set email alerts
|

Chinese shareholders’ reaction to the disclosure of environmental violations: a CSR perspective

Abstract: In the past decades, Corporate Social Responsibility (CSR) has attracted increasing attention, with Corporate Environmental Responsibility (CER or Environmental CSR) playing an ever important role. This paper aims to study whether and how Chinese shareholders are sensitive to the disclosure of environmental violations. Specifically, the issue is measured by the performance of the Chinese stock market. In order to answer this question, the authors conduct a two-dimensional "environment-as-a-resource" framework,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 19 publications
3
14
0
Order By: Relevance
“…Regarding Question 2, results were similar. Precisely, 59% of the respondents indicated that they had decided not to procure the products and services of firms that did not behave socially responsibly during the crisis, which supports the idea of punishing eco-harmful behaviour (Flammer 2013;Huang et al 2017). Only 23% of those surveyed indicated that the actions of companies during the crisis would not change their consumption habits (see Figure 2).…”
mentioning
confidence: 89%
“…Regarding Question 2, results were similar. Precisely, 59% of the respondents indicated that they had decided not to procure the products and services of firms that did not behave socially responsibly during the crisis, which supports the idea of punishing eco-harmful behaviour (Flammer 2013;Huang et al 2017). Only 23% of those surveyed indicated that the actions of companies during the crisis would not change their consumption habits (see Figure 2).…”
mentioning
confidence: 89%
“…In the same way, other authors (Jamali et al , 2008; Huang et al , 2014; Wang et al , 2020; Endrikat et al , 2020) regarded CSR as the integration of social and environmental concerns into firms’ activities and paying attention to stakeholders’ preoccupations. Thus, according to the generic definition set out above, CSR aims to integrate various corporate practices with the concept of social welfare to improve stakeholders’ benefits and promote the sustainable development of society (Branco and Rodriguez, 2006; Huang et al , 2017; Qiu et al , 2021; Javeed and Lefen, 2019; Franco et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to the efficient market hypothesis, the latest information will be reflected in the stock price, both positive and negative latest information will cause abnormal fluctuations in the stock price. Based on the efficient market hypothesis, researchers used the event study methodology to examine the impact of various adverse environmental events on the stock market, and found that the market will have a negative response to negative environmental events [4,9,15,16]. However, some researchers have come to different conclusions [12,17].…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Some studies found that shareholders' benefits will be negatively affected by accidental events [3][4][5][6][7]. The researchers found that the disclosure of environmental violation events will lower corporate estimated value [5,[8][9][10]. However, some researchers have come to different conclusions [11,12].…”
mentioning
confidence: 99%